VolumetricOR: A New Approach to Simulate Surgical Interventions in Virtual Reality for Training and Education. (June 2022) - Queisner, Moritz; Pogorzhelskiy, Michael; Remde, Christopher; Pratschke, Johann; Sauer, Igor M.
Background: Surgical training is primarily carried out through observation during assistance or on-site classes, by watching videos as well as by different formats of simulation. The simulation of physical presence in the operating theatre in virtual reality might complement these necessary experiences. A prerequisite is a new education concept for virtual classes that communicates the unique workflows and decision-making paths of surgical health professions (i.e. surgeons, anesthesiologists and surgical assistants) in an authentic and immersive way. For this project, media scientists, designers and surgeons worked together to develop the foundations for new ways of conveying knowledge using virtual reality in surgery. Materials and method: A technical workflow to record and present volumetric videos of surgical interventions in a photorealistic virtual operating room was developed. Situated in the virtual reality demonstrator called VolumetricOR, users can experience and navigate through surgical workflows as if they are physically present. The concept is compared with traditional video-based formats of digital simulation in surgical training. Results: VolumetricOR let trainees experience surgical action and workflows (a) three-dimensionally, (b) from any perspective and (c) in real scale. This improves the linking of theoretical expertise and practical application of knowledge and shifts the learning experience from observation to participation. Discussion: Volumetric training environments allow trainees to acquire procedural knowledge before going to the operating room and could improve the efficiency and quality of the learning and training process for professional staff by communicating techniques and workflows when the possibilities of training on-site are limited.